Faktor-Faktor yang Melatarbelakangi Orang Dewasa Mengikuti Program Pelatihan Komputer di LKP - Hidayat, Elsya Syamrotul; Mardhiyyah, Rodhiyyatan; Ashipa, Sarah Rumaisha (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Abstract. This research is motivated by the observed reality in the field, indicating that the computer course program for adults at IT Dadaha Training Course Institution (LKP) needs to prioritize the characteristics of adult learning assumptions. The course implementation primarily targets adults at the Dadaha IT Computer Training Course Institution (LKP), showing satisfactory execution. This is evident in the proficient instruction provided to adults and the supportive facilities and infrastructure. The study aims to achieve the following objectives: (1) describe the application of assumptions of adult learning experience in the execution of computer courses by instructors, (2) elucidate the application of assumptions of adult self-concept in the execution of computer courses by instructors, and (3) provide an account of the application of assumptions of adult learning readiness in the execution of computer courses by instructors. This descriptive research was conducted at the Dadaha IT Training Course Institute (LKP). Furthermore, it is suggested that future researchers explore different variables to enhance the study of adult learning readiness assumptions in computer course organization and to delve deeper into the examination of adult learning assumptions. Keyword: Application of learning, Computer Course.